PENGARUH PERILAKU INOVATIF, BEBAN KERJA DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN WARUNG SAK ADE ASLI GIANYAR - Dewa Ayu Nila Cahyani (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar., 2024)
Every company in carrying out its activities cannot be separated from employee performance. Employee performance greatly determines the success of achieving the goals of a company. Warung Sak Ade Asli Gianyar can be said to be one of the leading Traditional Shop in the culinary sector, but there are also employee performance problems. Many factors influence employee performance at Warung Sak Ade Asli Gianyar, including innovative behavior, workload and work discipline. This research aims to determine and prove the influence of innovative behavior, workload and work discipline on the performance of Warung Sak Ade Asli Gianyar employees. The research population was all employees of Warung Sak Ade Asli Gianyar, totaling 40 people. The sample consisted of 40 people who were determined based on the saturated sample method. The analysis technique used in this research is multiple linear regression analysis using the IBM SPSS Statistics 26 application. The results of this research show that 1) Innovative behaviour have a positive and significant effect on employee performance at Warung Sak Ade Asli Gianyar. 2) Workload have a positive and significant effect on employee performance at Warung Sak Ade Asli Gianyar. 3) Work discipline have a positive and significant effect on employee performance at Warung Sak Ade Asli Gianyar.